Jasmone Is a Ligand-Selective Allosteric Antagonist of Aryl Hydrocarbon Receptor (AhR) - Vrzal, Radim; Marcalíková, Adéla; Krasulová, Kristýna; Zemánková, Lenka; Dvořák, Zdeněk (International journal of molecular sciences, 2023)
Herbal extracts represent a wide spectrum of biologically active ingredients with potential medical applications. By screening minor constituents of jasmine essential oil towards aryl hydrocarbon receptor (AhR) activity using a gene reporter assay (GRA), we found the antagonist effects of jasmone (3-methyl-2-[(2Z)-pent-2-en-1-yl]cyclopent-2-en-1-one). It inhibited 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-, benzo[a]pyrene (BaP)-, and 6-formylindolo[3,2-b]carbazole (FICZ)-triggered AhR-dependent luciferase activity in a concentration-dependent manner. However, the inhibition differed markedly between TCDD, BaP, and FICZ, with the latter being significantly less inhibited. The dose-response analysis confirmed an allosteric type of AhR antagonism. Furthermore, jasmone efficiently inhibited AhR activation by AhR agonists and microbial catabolites of tryptophan (MICTs). TCDD- and FICZ-inducible CYP1A1 expression in primary human hepatocytes was inhibited by jasmone, whereas in the human HepG2 and LS180 cells, jasmone antagonized only TCDD-activated AhR. Jasmone only partially displaced radiolabeled TCDD from its binding to mouse Ahr, suggesting it is not a typical orthosteric ligand of AhR. TCDD-elicited AhR nuclear translocation was not affected by jasmone, whereas downstream signaling events, including the formation of the AhR:ARNT complex and enrichment of the CYP1A1 promoter, were inhibited by jasmone. In conclusion, we show that jasmone is a potent allosteric antagonist of AhR. Such discovery may help to find and/or clarify the use of jasmone in pharmaco- and phytotherapy for conditions where AhR plays a key role.
Keywords: ligandy; HepG2; Polychlorinated Dibenzodioxins; Receptors, Aryl Hydrocarbon; Mice; cytochrom P-450 CYP1A1; Ligands; zvířata; Humans; jasmone; AhR; myši; CYP1A1; polychlorované dibenzodioxiny; receptory aromatických uhlovodíků; ChIP; LS180; lidé; Cytochrome P-450 CYP1A1; Animals